The shape of spectatorship : art, science, and early cinema in Germany. - Curtis, Scott (New York, NY : Columbia University Press, 2015)
In this exceptionally wide-ranging study, Scott Curtis draws our eye to the role of scientific, medical, educational, and aesthetic observation in shaping modern conceptions of spectatorship. Focusing on the nontheatrical use of motion picture technology in Germany between the 1890s and World War I, he follows specialists across disciplines as they debated and appropriated film for their own ends, negotiating the fascinating, at times fraught relationship between technology, discipline, and expert vision.
Introduction -- Science's cinematic method: motion pictures and scientific research -- Between observation and spectatorship: medicine, movies, and mass culture -- The taste of a nation: educating the senses and sensibilities of film spectators -- The problem with passivity: aesthetic contemplation and film spectatorship -- Conclusion: toward a tactile historiography.
Includes bibliographical references and index.
Print version record.
In English.
JSTOR
Keywords: Motion pictures -- Germany -- History -- 20th century; Motion picture audiences -- Germany -- History -- 20th century; Motion pictures -- Aesthetics; Motion pictures in science -- Germany; Documentary films -- Germany -- History -- 20th century; Cinéma -- Allemagne -- Histoire -- 20e siècle.; Cinéma -- Publics -- Allemagne -- Histoire -- 20e siècle.; Cinéma -- Esthétique.; Cinéma en sciences -- Allemagne; Documentaires -- Allemagne -- Histoire -- 20e siècle.; PERFORMING ARTS -- Reference; EDUCATION / History; Documentary films; Motion picture audiences; Motion pictures; Motion pictures -- Aesthetics; Motion pictures in science; Germany; Film; Deutschland; 1900-1999; Electronic book; History